In vitro, acute and subchronic evaluation of the antidiabetic activity of Atractylis flava Desf n-butanol extract in alloxan-diabetic rats - Mohamed Akram Melakhessou; Salah Eddine Marref; Naima Benkiki; Cherine Marref; Imene Becheker; Latifa Khattabi (SpringerOpen, 2021)
Abstract Background Diabetes mellitus is a serious complex multifactorial disorder that imposes huge health and economic burden on societies. Because the currently available medications have many drawbacks, it's important to look for alternative therapies. Medicinal plants utilized in folk medicine are ideal candidates. Therefore, this work assessed the antidiabetic action of n-butanol extract from the whole plant Atractylis flava Desf (BEAF). These ethnomedicinal properties of BEAF were scientifically validated using in vitro and in vivo assays. In vitro antidiabetic effect of the BEAF was conducted using α-Glucosidase and α-Amylase assays. While the antihyperglycemic activity was assessed using two rat models: Alloxan-induced diabetic rats and oral glucose challenged rats. Experimental diabetes was induced by a single intraperitoneal injection of alloxan at a dose of 150 mg/kg and animals with fasting blood glucose levels (BGL) > 200 mg/dL were considered diabetic. Glibenclamide (5 mg/kg) was used as a typical drug. Results The BEAF at all tested dose levels (100, 250, and 500 mg/kg) showed a significant decrease in blood glucose level in all the two animal models. Besides, the plant extract exhibited a potent inhibitory effect on α-Amylase and α-Glucosidase activity at a concentration of 1000 µg/mL with 76.17% and 89.37%, respectively. Conclusion BEAF exerts in vitro and in vivo antidiabetic effects, these results suggest that the plant extract can be a therapeutic resource in the treatment of diabetes and hyperlipidemia.